Growing up to God : a guide for teenagers on the sacrament of reconciliation - Pastva, Mary Loretta; Romancik, Mary Roy.; Stanko, Mary Dolores (New York : Alba House, 1983)
A discussion of the Sacrament of Penance and how to make it meaningful.
Includes bibliographical references.
Keywords: Catholic Church -- Doctrines -- Juvenile literature; Catholic Church; Penance -- Juvenile literature; Youth -- Religious life; Penance; Reconciliation; Sacraments -- Catholic Church